Electromagnetic detection of a perfect invisibility cloak - Zhang, Baile (2012)
A perfect invisibility cloak is commonly believed to be undetectable from electromagnetic (EM) detection because it is equivalent to a curved but empty EM space created from coordinate transformation. Based on the intrinsic asymmetry of coordinate transformation applied to motions of photons and charges, we propose a method to detect this curved EM space by shooting a fast-moving charged particle through it. A broadband radiation generated in this process makes a cloak visible. Our method is the only known EM mechanism so far to detect an ideal perfect cloak (curved EM space) within its working band.